Awareness Ayah atas Perkembangan Agama Anak 5-6 Tahun di Kalangan Nelayan Pulau Jinato Selayar - Nurmiati, Nurmiati; Rahman, Ulfiani; Hamansah, Hamansah; Ismail, Wahyuni; Afiif, Ahmad (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to understand the form of father's attention, inhibiting and supporting factors, and the impact of father's awareness on children's religious development. The research method used is qualitative descriptive. Primary data was obtained from interviews with fishermen's fathers, while secondary data came from village profiles, journals, and related documents. Data analysis is carried out through data reduction, coding, presentation, and drawing conclusions. The results showed variations in the form of fatherly attention. There are fathers who pay great attention to the development of children's religion, but there are also those who leave it completely to the mother or teacher. Factors that inhibit father's consciousness include a lack of time and religious knowledge, while the supporting factors are the role of teachers and the existence of Islamic boarding schools. The impact of the father's lack of awareness is the lack of religious stimulation in the child. This study concludes the importance of education for fisherman fathers about the importance of providing religious education to early childhood. The implication of this research is the need for educational programs for educators and further research on the introduction of monotheism in early childhood. This research also provides a comprehensive overview of the situation on the ground and provides recommendations to improve the quality of religious education for children on Jinato Island